Multi-Substrate Biofuel Cell Utilizing Glucose, Fructose and Sucrose as the Anode Fuels - Michał Kizling; Maciej Dzwonek; Anna Nowak; Łukasz Tymecki; Krzysztof Stolarczyk; Agnieszka Więckowska; Renata Bilewicz (Nanomaterials, 2020)
A significant problem still exists with the low power output and durability of the bioelectrochemical fuel cells. We constructed a fuel cell with an enzymatic cascade at the anode for efficient energy conversion. The construction involved fabrication of the flow-through cell by three-dimensional printing. Gold nanoparticles with covalently bound naphthoquinone moieties deposited on cellulose/polypyrrole (CPPy) paper allowed us to significantly improve the catalysis rate, both at the anode and cathode of the fuel cell. The enzymatic cascade on the anode consisted of invertase, mutarotase, Flavine Adenine Dinucleotide (FAD)-dependent glucose dehydrogenase and fructose dehydrogenase. The multi-substrate anode utilized glucose, fructose, sucrose, or a combination of them, as the anode fuel and molecular oxygen were the oxidant at the laccase-based cathode. Laccase was adsorbed on the same type of naphthoquinone modified gold nanoparticles. Interestingly, the naphthoquinone modified gold nanoparticles acted as the enzyme orienting units and not as mediators since the catalyzed oxygen reduction occurred at the potential where direct electron transfer takes place. Thanks to the good catalytic and capacitive properties of the modified electrodes, the power density of the sucrose/oxygen enzymatic fuel cells (EFC) reached 0.81 mW cm−2, which is beneficial for a cell composed of a single cathode and anode.